2018
DOI: 10.1016/j.str.2018.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination against RNA Backbones by a ssDNA Binding Protein

Abstract: Pot1 is the shelterin component responsible for the protection of the single-stranded DNA (ssDNA) overhang at telomeres in nearly all eukaryotic organisms. The C-terminal domain of the DNA-binding domain, Pot1pC, exhibits non-specific ssDNA recognition, achieved through thermodynamically equivalent alternative binding conformations. Given this flexibility, it is unclear how specificity for ssDNA over RNA, an activity required for biological function, is achieved. Examination of the ribose-position specificity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“… 35 ), which have suggested that the nucleic acid-binding interface is malleable. For example, single-stranded recognition interfaces can be remodeled to match different substrates to achieve specific recognition for both DNA and RNA, as exemplified by the Oxytricha nova telomere end-binding protein ( 36 ), the S. pombe Pot1 protein ( 28 , 37 ), and, in RNA recognition, the PUF protein ( 38 ) and the MS2 coat protein ( 39 ). This malleability could be dynamic in origin ( 40 , 41 ).…”
Section: Discussionmentioning
confidence: 99%
“… 35 ), which have suggested that the nucleic acid-binding interface is malleable. For example, single-stranded recognition interfaces can be remodeled to match different substrates to achieve specific recognition for both DNA and RNA, as exemplified by the Oxytricha nova telomere end-binding protein ( 36 ), the S. pombe Pot1 protein ( 28 , 37 ), and, in RNA recognition, the PUF protein ( 38 ) and the MS2 coat protein ( 39 ). This malleability could be dynamic in origin ( 40 , 41 ).…”
Section: Discussionmentioning
confidence: 99%